2021
DOI: 10.21203/rs.3.rs-611789/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fungal-bacterial biofilm mediated heavy metal rhizo-remediation

Abstract: Heavy metal pollution due to excessive use of chemical fertilizers (CF) causes a major damage to the environment. Microbial consortia, closely associated with the rhizosphere are able to remediate heavy metal-contaminated soil by reducing plant toxicity. Thus, this study was undertaken to examine the remedial effects of microbial biofilms against contaminated heavy metals. Fungi and bacteria isolated from soil were screened for their tolerance against Cd2+, Pb2+ and Zn2+. Fungal-bacterial biofilms (FBBs) were … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…Filamentous fungi can be considered as biofilm-forming organisms as they naturally adapted to grow on surfaces [37]. The production of EPS by fungal mycelium has the potential to increase EPS production in FBBs [24,8]. In the current study, microscopic observation indicated high EPS secretion by FBBs (Fig.…”
Section: Qualitative and Quantitative Analysis Of Ethanol Production ...supporting
confidence: 49%
“…Filamentous fungi can be considered as biofilm-forming organisms as they naturally adapted to grow on surfaces [37]. The production of EPS by fungal mycelium has the potential to increase EPS production in FBBs [24,8]. In the current study, microscopic observation indicated high EPS secretion by FBBs (Fig.…”
Section: Qualitative and Quantitative Analysis Of Ethanol Production ...supporting
confidence: 49%